Method and apparatus for testing driver circuits of AMOLED - Tsai, Shan-Hung; Sun, Ming-Hsien; Shih, An (2004)
A method and an apparatus for testing a plurality of driver circuits of an AMOLED before OLEDs are implanted are provided. The method and the apparatus select one specific driver circuit to be tested and dispose a conductive board above the array glass of the OLED to form a capacitor. By using the data line, the scan line, and the power line of an AMOLED, the present invention is able to input and retrieve signals from driver circuits for analyzing each of them is normal or not.